Enigmas of Health and Disease : How Epidemiology Helps Unravel Scientific Mysteries - ALFREDO MORABIA (Columbia University Press, 2014)
The book you are reading is the English adaptation of my 2011 French book entitled Santé: Distinguer croyances et connaissance. My original approach to translating Santé had been to remain faithful to its words, style, and syntax. This proved ineffective, however, because it ignored a key component of language: the cultural context. While I am writing now, each word comes to my mind with a choice of synonyms, reminiscent of books, songs, or poems. In both French and English, words, expressions, and syntax flexibility are nested in different sets of cultural and literary connections. On top of this, English-speaking societies are more familiar with epidemiology than French-speaking ones and therefore necessitate different narration. My last incentive to adapt rather than translate Santé is more personal. I had grown tired of reading the same prose in both English and French and yearned to feel the same excitement from the English version I had from the book in French. The result is that although Santé and Enigmas of Health and Disease cover the same topics and develop the same ideas, each book has its own distinct character.